Capacity Building in Geo-information Sector: A Case of Kathmandu University - Ghimire, Subash (Journal on Geoinformatics, Nepal, 2016)
Capacity building in Geo information is the empowerment that encompasses the ability, skills to initiate, manage, undertake, organize and evaluate Geoinformation activities. The capacity building includes major elements such as education, training, research, informal approaches such as networking, refresher courses, seminar/ conference. This paper aims to highlight the role of Kathmandu University (KU) for capacity building in Geo information sector in Nepal. It is committed to develop a center of excellence in Geoinformation sector by providing quality education, research, training etc. Kathmandu University, Geomatics Engineering program has collaboration with academic and nonacademic organizations to strengthen the quality of geoinformation education, research and internship. KU has also planned for the capacity building of faculty and students through its faculty development plan and student exchange program with other collaborating Universities. Geo spatial lab and other important advanced survey; Geodesy, remote sensing, photogrammetry lab etc. will be developed in near future at KU premises. LMTC and KU are also jointly establishing the necessary infrastructure required for the Geomatics Engineering program in the vicinity of these two organizations.